Intermediate and expanded FMR1 alleles in an autistic Costa Rican population - Vindas Smith, Rebeca (2022)
Objective: We aimed to determine the distribution of intermediate and expanded FMR1 alleles in Costa Rican individuals diagnosed with autism. Materials and methods: A total of 212 autism spectrum disorder (ASD) cases of Costa Rican individuals and 943 male newborn controls were screened by means of polymerase chain reaction to determine the frequency of intermediate, premutation, and full mutation FMR1 alleles. Full mutation suspected cases were confirmed by Southern blot analyses. Frequencies of FMR1 alleles in the case group were compared with frequencies observed in a population-based sample of male newborn controls. Results: A significant excess of intermediate allele carriers was found in ASD individuals as compared to controls (χ2 test, p < 0.001). Four, out of 188 males in the case group, were identified as full mutation carriers. Conclusions: Our results suggest a possible involvement of the gray zone or intermediate alleles in ASD.